FLASHBACK OF THE MOSQUE IN HISTORY: FROM THE PROPHET'S PERIOD TO THE ABASIYYAH DYNASTY - Abid Nurhuda; Dewi Sinta; Inamul Hasan Ansori; Nur Aini Setyaningtyas (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2023)
Education and teaching in Islamic history have started since the Prophet received the first revelation in Mecca. When the Prophet migrated to Medina, he founded a mosque as the center of Muslim activity. Thus, this study aims to describe the Flashback of the Mosque in the Trajectory of History. The method used is a literature study with a historical-theological approach, which was then analyzed descriptively and concluded. The results of the study show that the Flashback of the Mosque in the Trajectory of History at the time of the Prophet was very simple but meaningful because it was used as a center for the spiritual development of faith, economy, education, politics, cultural arrangement and all forms of human social order. Then, during the time of the companions, the Mosque underwent physical development, starting from the expansion of buildings to the construction of new mosques in areas successfully conquered by the Muslims, even though the roles and functions were still the same as those of the Prophet Muhammad. Then, during the Umayyad and Abasiyyah periods, mosques experienced rapid progress in infrastructure and art, where towering towers and large mosque domes appeared. Still, their role and function decreased because they were only used as religious centers.